Biomechanics in liver regeneration after partial hepatectomy - Wu, Yi; Li, Ning; Shu, Xinyu; Li, Wang; Zhang, Xiaoyu; Lü, Dongyuan; Long, Mian (Frontiers in Bioengineering and Biotechnology, 2023)
The liver is a complicated organ within the body that performs wide and vital functions, and also has a unique regenerative capacity after hepatic tissue injury and cell loss. Liver regeneration from acute injury is always beneficial and has been extensively studied. Experimental models including partial hepatectomy (PHx) reveal that extracellular and intracellular signaling pathways can help the liver recover to equivalent size and weight prior to injury. In this process, mechanical cues possess immediate and drastic changes in liver regeneration after PHx and also serve as main triggering factors and significant driving forces. This review summarized the biomechanics progress in liver regeneration after PHx, mainly focusing on PHx-based hemodynamics changes in liver regeneration, as well as the decoupling of mechanical forces in hepatic sinusoids including shear stress, mechanical stretch, blood pressure and tissue stiffness. Also discussed were the potential mechanosensors, mechanotransductive pathways and mechanical responses under varied mechanical loading in vitro. Further elucidating these mechanical concepts in liver regeneration helps establish comprehensive understandings between biochemical factors and mechanical cues in this process. Proper adjustment of mechanical loading within the liver might preserve and restore liver functions in clinic, serving as an effective therapy for liver injury and diseases.